2013
DOI: 10.5588/pha.12.0077
|View full text |Cite
|
Sign up to set email alerts
|

Peanut-based ready-to-use therapeutic food: acceptability among malnourished children and community workers in Bangladesh

Abstract: with a community-based nutrition programme that has been using PPN for the management of acute malnutrition among children in a slum setting in Dhaka, Bangladesh. Bangladesh has one of the highest prevalence rates of childhood malnutrition in the world: 6,7 almost 46% of children aged <5 years are stunted (low height for age) and 15% are wasted (low weight for height). 8 During the implementation of this nutrition programme, several care givers of children complained of diffi culties in feeding their childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 11 publications
3
24
4
Order By: Relevance
“…Multiple acceptability trials in South Asia have shown limited acceptability of RUTF and demonstrate a need for more culturally accepted ingredients and formulations (Ali et al . ; Nga et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple acceptability trials in South Asia have shown limited acceptability of RUTF and demonstrate a need for more culturally accepted ingredients and formulations (Ali et al . ; Nga et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…While a recent study has shown that LNS has poor acceptability of LNS among malnourished children in South Asia (Ali et al . ), some studies in Africa have shown that LNS has an excellent acceptability by the children (Flax et al . ; Hess et al .…”
Section: Discussionmentioning
confidence: 99%
“…Two caregivers in Ethiopia specifically mentioned their child disliked the texture of RUTF and two mentioned that the taste was unacceptable; however, these limited data do not indicate a clear trend. Some evidence suggests that RUTF palatability varies according to traditional dietary differences and this remains a subject of debate (34)(35)(36) . However, given that most caregivers in this setting were able to overcome the barrier of RUTF refusal, particularly after receiving counselling, this issue potentially could be remedied in this setting by reinforced training in administering appetite tests, negotiation skills and improved counselling on proper feeding of RUTF.…”
Section: Discussionmentioning
confidence: 99%